A first step to assess suspended microplastics in a freshwater wetland from the coastal region of Ecuador - López, Carlos; Soto, Luz Marina; Acosta, Vanessa; Santana-Piñeros, Ana María; Cruz-Quintana, Yanis; Gomes-Barbosa, Luciana; Stamou, Georgia; Karpowicz, Maciej; Michaloudi, Evangelia; Domínguez-Granda, Luis; Steinitz-Kannan, Miriam (Frontiers in Environmental Science, 2023)
La Segua is an important wetland in Ecuador, recognized as a Ramsar site and of great ecological relevance. Currently, La Segua is threatened by human pressures and unsustainable landscape use associated with agriculture and aquaculture. This study is the first approach to the occurrence of suspended microplastics (SMPs) in an Ecuadorian lentic waterbody and the estimated potential threat of these on the filter and suspension feeders in aquatic food webs. Surface water samples were collected at 16 sampling points in the wetland to analyze the occurrence, concentration, and horizontal distribution of Suspected Suspended Microplastics (SSMPs) and zooplankton. SSMPs were found in all sampling sites, and concentrations were between 313 and 490 particles/liter. Fragments were the most abundant category, followed by fibers, films, and pellets. The highest concentration of SSMPs was found in sampled sites on the east coast and in the middle of the wetland. The frequency and concentration of categories of SSMps found in surface water largely reflect the reality of local human activity around the La Segua wetland. Only rotifers and copepod nauplii were found in the zooplankton. The SSMPs to zooplankton ratio varied between 0.3 and 441 particles/individuals. The SSMPs/zooplankton ratio indicates that fish and other filter and suspension feeders of aquatic food webs could be more likely to feed on suspended microplastics than natural food items around the wetland. SSMPs indicate that microplastics may represent a threat to the stability and efficiency of the food webs in this wetland and may negatively affect fisheries and aquaculture activities, and other ecosystem services